Pelatihan Diversifikasi Produk Dan Strategi Digital Marketing Untuk Meningkatkan Pendapatan Masyarakat Desa Nipa Kecamaan Ambalawi - Nurul Huda; Jaenab; Muhammad Yusuf; Miftahul Tazqiah Auliya; Kiki Anggriani; Aerlangga (Indo Publishing, 2025)
Nipa Village in Ambalawi District, Bima Regency, West Nusa Tenggara Province possesses substantial natural resource potential in the fisheries and agricultural sectors; however, this potential has not been fully directed toward the development of value-added processed products. This community service program aims to enhance the knowledge and skills of community business groups in processing, packaging, marketing, and business management based on local commodities, particularly fishery and agricultural products. The program was implemented through a series of training sessions and mentoring activities covering food product processing, packaging innovation, branding, and offline and online marketing strategies, involving community business actors, village officials, and students participating in a Community Service Program (KKN) accompanied by supervising lecturers. The results indicate an increase in entrepreneurs’ understanding of basic entrepreneurial concepts, more structured business management, and the ability to develop processed products based on local commodities with more attractive and competitive packaging. In addition, the use of digital technology in marketing has begun to be adopted by business actors, opening opportunities for market expansion and income improvement. Overall, this program contributes to strengthening the local economy of Nipa Village through optimizing the management of natural resource potential and developing community-based business units.